Identification of chemical species created during γ‐irradiation of antioxidant used in polyethylene and polyethylene‐co‐vinyl acetate multilayer film. Issue 43 (7th May 2020) - Dorey, Samuel; Gaston, Fanny; Girard‐Perier, Nina; Dupuy, Nathalie; Marque, Sylvain R.A.; Barbaroux, Magali; Audran, Gérard
Abstract: With the increasing use of γ‐irradiated containers made of multilayer polymeric flexible films for food and biopharmaceutical applications, the possible migration of degradation products of the polymers and their additives is becoming a topic of concern. This article aims at highly reliably identifying the degradation products generated after gamma irradiation and their origin to later on assess their potential harmfulness in single‐use containers. In this study, GC–MS is used to identify by‐products created by γ‐irradiation of primary and secondary antioxidants usually present in polyolefin‐based biotechnological single‐use materials and to confirm identification relevancy based on the literature survey or standard when available. Degradation pathways are proposed to account for the formation of by‐products identified during the study and to list intermediates and other by‐products present in too small amounts to be detected and identified accurately in all extractable studies. Abstract : This article aims at identifying degradation products of gamma‐irradiated multilayer polymer films used in food and biopharmaceutical domains. For that, GC–MS was used to identify by‐products of antioxidants usually present in single‐use materials. Degradation pathways were then proposed to account for the formation of these by‐products.